A 64 ​dBΩ, 25 ​Gb/s GFET based transimpedance amplifier with UWB resonator for optical radar detection in medical applications. (May 2021) - Gorre, Pradeep; Vignesh, R.; Song, Hanjung; Kumar, Sandeep
Abstract: This work reports a novel Graphene Field Effect Transistor (GFET) based transimpedance amplifier (TIA) for optical radar detection in medical applications. Design-I includes a microstrip line (MSL) based UWB resonator circuit which enables the TIA design to operate in UWB range of frequency with high Q-factor. Design-II comprises MSL UWB resonator integrated stagger-tuned CR-RGC TIA which enhances the transimpedance limit and mitigates the effect of photodiode capacitance results in higher bandwidth performance. The proposed TIA realizes a 2.6 times lesser noise compared to the conventional CR-RGC TIA. A flat transimpedance gain of 64 ​dBΩ and ultra-low input-referred noise current density of 8.9 pA/√Hz are achieved using gain and noise optimization methods. Additionally, a dynamic range of 49 ​dB with a group delay variation (GDV) of ±25 ps is achieved over the entire UWB range. The TIA demonstrates a 25 ​Gb/s data rate while a bit-error-rate (BER) less than 10 −10 is achieved. The chip occupies an area of 0.67∗0.72 ​mm 2 while consuming power of 19 ​mW under the supply voltage of 1.8 ​V.